Peningkatan Kompetensi Guru dalam Mengembangkan Asesmen Berbasis Keterampilan Abad 21 Melalui Kelompok Kerja Kepala Sekolah Kecamatan Semarang Barat - Sri Wardani; Sri Haryani; Joni Albar; Deden Dicky Dermawan; Jumardan Jumardan (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
Assessment development is an important component in 21st-century learning. Therefore, teachers are required to be able to develop 21st-century skills-based assessments or assessments for students. This service research aims to improve teacher competence in developing 21st-century skills-based assessments through the working group of school principals in West Semarang District. Participants in this community service activity are members of the working group of school principals consisting of elementary school teachers in the West Semarang District. The methods used in this service are the lecture method, experiment/practice, and task method. The impact of these service activities is in the form of increasing teacher understanding related to 21st-century skills. In addition, teachers have a broader and deeper insight into 21st-century competencies, and teacher competencies in compiling and developing 21st-century competency-based assessments can be integrated into the form of multiple-choice tests and essay tests.